Juvenile Delinquency in India Causes and Prevention: Understanding the Causes and Impact of Juvenile Delinquency in Indian Society (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Juvenile delinquency is an enormous problem in India by which most of the youth ruin their lives. Because of juvenile crime and relate problems youth, their families and the entire society suffer multiple consequences. Not only does the problem affect the victims of the crime it also affects the juvenile delinquents family, their future, and the society as a whole. The most obvious people affected by juvenile delinquency are the victims. The most profound consequence of crimes committed by juveniles carries due to socio-economic and psychological problems which reflect on their family members and the society. Due to the psychological problems, sometimes juveniles involved in robberies, rapes and assaults also are significant. With these criminal activities the juveniles habituate to consume alcohol or other drugs. The main objective of this paper is to study the incidence of juvenile delinquency with reference to psychological perspectives. The juvenile who commit serious crimes challenge their future to protest perceived abuses that have been perpetrated against them. This makes them psychological depression and in turn reflects to commit more crimes. In this circumstance the study on incidence of juvenile delinquency is very important to analyze the causes with reference to psychological perspectives and annihilate in the society.